Role of Training in Women Empowerment: An Empirical Analysis: Women Empowerment - Tiwari, Pratiksha; Malati, Nittala (Journal of Technical Education and Training, 2023)
India is progressing economically, but it needs to pay more attention to social and human development together with women empowerment. The economic contribution and empowerment of women are pertinent to strengthen female’s rights and enable them have control on their lives and influence the society.   Sustainable development can be achieved through economic empowerment of women.  Empowered women and gender equality lead in multiplying the development efforts. Under the SDG-5, India has stated that it will ensure women and girls contribute as equivalent partners to growth and development of the country by 2030. At the global level too, it has been observed that if women participate equally with men in the economic activity, the world will add $11 trillion in the annual 2025 GDP.  Investing on education and skill enhancement through Vocation education and training. has been a pertinent issue for the Indian government for the last decade. The current paper identifies the constructs of women empowerment and observes the role of formal and informal training in female empowerment. In all 317 women participated in the study through two stage sample design involving area sampling followed by convenience sampling. The study identified five constructs of women empowerment Economic Empowerment, Family Health and Well Being, Civic Empowerment, Social Empowerment, Educational Empowerment through exploratory factor analysis confirmed through confirmatory factor analysis. Further, the mean scores of all the constructs of women empowerment for formally trained respondents were higher than informally trained respondents but no significant difference between women empowerment, constructs of formally and informally trained women observed in the study.